ANTI-OXIDANT AND ANTI-INFLAMMATORY POTENTIAL OF SECONDARY METABOLITES FROM Daphne mucronata ROYLE AND THEIR FIRST-PRINCIPLES INVESTIGATIONS - Imran, Muhammad; Irfan, Ahmad; Hussain, Sajjad; A. Assiri, Mohammed; Uddin, Jalal; Hussain, Ajaz; Khalid, Noreen; G. Al-Sehemi, Abdullah (Journal of the Chilean Chemical Society, 2021)
Ten coumarin class of compounds, including new fused coumarinolignoids namely, mucronin-C (1) were isolated from the methanol extract from whole plant of Daphne mucronata Royle. The structures of mucronin-C (1) and its configurations were determined by chemical and spectroscopic methods including 1DNMR, 2D-NMR and HR-FAB-MS. The isolated compounds 1-10 were evaluated for in-vitro biological activities. The anti-inflammatory (lipoxygenase) activities of compound 1, 4, 8, 9 and 10 (IC50 = 21.7, 23.7, 25.1, 27.3 and 26.0 µg/mL, respectively) were higher compared with standard Quercetin (IC50 = 22.5 µg/mL). The antioxidant property of coumarin as evaluated by DPPH scavenging bioassay was significantly greater in compounds 1-5, 9 and 10 (IC50 = 0.7, 0.8, 1.9, 2.3, 2.8, 0.5 and 2.1 µg/mL respectively) as standard Trolox (IC50 = 0.3 µg/mL). The density functional descriptors in the progress of quantitative structure-activity relationship (QSAR) are significant to analyze the reactive sites and antioxidant ability of compounds. We have explored the reactive sites and radical scavenging activity of studied coumarin derivatives by shedding light on electron affinity, ionization potential, molecular electrostatic potential, frontier molecular orbitals and molecular descriptors analysis. First-principles calculations about one-electron transfer mechanism revealed that smaller ionization potential value of Compounds 1-5, 9 and 10 are leading to superior antioxidant activity, which is in good agreement with the experimental data.